Investigation of microwave-assisted pyrolysis of biomass with char in a rectangular waveguide applicator with built-in phase-shifting. (1st February 2020) - Ellison, Candice Raffaela; Hoff, Ryan; Mărculescu, Cosmin; Boldor, Dorin
Highlights: Microwave biomass pyrolysis was accelerated by addition of biochar as an absorber. Continuous EM field phase shifting enabled uniform heating within the biomass. Increased conversion to noncondensable gases was observed at greater absorbed power. Bio-oil was dominated by phenols w/increasing polyaromatic content at high powers. Abstract: Fast biomass pyrolysis is a promising technique for thermochemical conversion of biomass into chemicals and biofuels (bio-oil and syngas). Microwave heating can increase process efficiency. The effect of microwave absorber and microwave power level are studied for their effect on pyrolysis process temperature, product yields, and product composition. A novel microwave system was designed with a continuous sliding short enabling phase shifting to mitigate standing wave effects in the low loss load. Pyrolysis experiments on pine sawdust were carried out at varying microwave input powers (600, 900, 1200, and 1500 W) and with varying amounts of biochar added to the feedstock (0, 10, and 20% by weight) in a 4 × 3 full factorial experimental design. Pine sawdust without the aid of microwave absorber failed to reach pyrolysis temperatures by dielectric heating, only reaching 200 °C even at 1500 W power. Pyrolysis yields were correlated to absorbed power rather than input power as temperature is more strongly correlated to absorbed power. Addition of biochar was found to have a significant effect on the absorbed powers and resulting pyrolysis temperatures, increasing temperatures 4 fold from 0% to 10% char, however, no significant difference was found when char mixture was increased from 10 to 20%. Yields of char decreased with increasing absorbed microwave power, while non-condensable gas increased, indicating increased thermal cracking to non-condensable gases with increasing process temperature. Water-free bio-oil yields were found to increase with absorbed power. The liquid product from microwave pyrolysis of pine sawdust is composed primarily of phenols, with little changes in yield at all absorbed powers. Carbonyl functional groups and furans decreased while polyaromatics increased with increasing absorbed power due to the increased decomposition of lignin. The greatest net energy yields were observed for pyrolysis run at 900 W applied microwave power and 20% char.